Dachshund : the hot dogger - Lunis, Natalie (New York : Bearport Pub., 2009)
Provides an introduction to Dachshunds that discusses the breed's history, physical characteristics, and behaviors and looks at Dachshunds in popular culture.
Includes bibliographical references (p. 31) and index.
5.0
3-6
Keywords: Dachshunds -- Juvenile literature; Dachshunds; Dogs; Dachshunds; Dogs